Development of a nomogram for predicting the stone‐free rate after transurethral ureterolithotripsy using semi‐rigid ureteroscope. (19th November 2012) - Imamura, Yusuke; Kawamura, Koji; Sazuka, Tomokazu; Sakamoto, Shinichi; Imamoto, Takashi; Nihei, Naoki; Suzuki, Hiroyoshi; Okano, Tatsuya; Nozumi, Kuniyoshi; Ichikawa, Tomohiko
<x xml:space="preserve">Abstract</x> Objectives To develop and to internally validate a novel nomogram for predicting the stone‐free rate after transurethral ureterolithotripsy. Methods A total of 412 patients with 534 ureteral stones were treated with transurethral ureterolithotripsy using semi‐rigid ureteroscopes. Treatment efficacy was evaluated 3 months after the procedure. Multivariate stepwise logistic regression analysis was used to identify independent predictors of being stone‐free in the model‐building set. A total of 427 stones (80% of 534) were randomly allocated for identification and statistical analysis to build the model, and the remaining 107 (20%) were used for cross‐validation. A nomogram for the stone‐free rate was developed based on the final logistic regression model. Results Stone length, number of stones, stone location and the presence of pyuria were independent factors related to the stone‐free rate after transurethral ureterolithotripsy treatment, and these were used to develop a nomogram. In this nomogram, the area under the receiver operating characteristic curve was 0.7432 for the nomogram, 0.5641 for stone size, 0.5908 for the number of stones, 0.6594 for stone location and 0.6076 for pyuria. Validation using 20% of the data also achieved a reasonable predictive accuracy (area under the receiver operating characteristic curve = 0.682). Conclusions The first nomogram for predicting the stone‐free rate after transurethral ureterolithotripsy was developed. It has a reasonable predictive accuracy, and in combination with extracorporeal shock wave lithotripsy nomograms, it might be useful for deciding treatment methods.